AL-FARABI ON THE STATE AND POLITICS - Prasetyo, Adi (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2019)
The concept of Al-Farabi’s thought about Syahsiyah Al-Madaniyyah and Ara’al-Madinah Al-Fadhilah is included in political thought. In this writing, the writer presents Al-Farabi’s works related to his political thinking from a combination of Platonic, Aristotelian, and Islamic concepts. In his political theory, Al-Farabi stressed that happiness for citizens must be emphasized, and that is the primary goal of the state. According to Al-Farabi, governance in a country is like a complementary body element to one another to create a common goal in the state. This means that just as one member of the community suffers, the suffering is also felt by other members of the community itself. The ideal (ethical) leadership, according to Al-Farabi, is to emphasize the role, the right function aims to form a state leader following the ideal image of humanity. The ideal state for Al-Farabi is the existence of a goal that is prosperous for its citizens, and the foremost leader in the state is a philosopher who possesses p